Spatial and temporal analysis of land use/land cover using remote sensing of Lucknow district, Uttar Pradesh, India - Vijay Kumar Singh Rathore,; Anjani Kumar Singh,; Anil Kumar Tiwari, (National Geographical Journal of India, 2024)
The combined forces of population and economic growth have driven the urbanization process over the past four decades, leading to substantial changes in land use and land cover (LULC) in the Lucknow district of Uttar Pradesh. This paper examines the LULC changes using geospatial techniques on a decadal basis from 1980 to 2020. Landsat imageries from 1980, 1990, 2000, 2010, and 2020 are used and categorized into five land use classes: agricultural land, built-up areas, water bodies, tree cover, and wasteland. The classification is done using supervised maximum likelihood classification algorithms, and the accuracy was satisfactory for further analysis. The classified images are then overlaid in a Geographic Information System (GIS) environment to assess decadal LULC changes and to generate LULC change matrices for the periods 1980-1990, 1990-2000, 2000-2010, and 2010-2020. The analysis of LULC statistics from each classified image reveals significant changes in all land use classes over the study period. There has been a decreasing trend in agricultural land, water bodies, and wastelands, while built-up areas and tree cover have shown an increasing trend. The built-up area class has experienced the highest positive change rate, followed by tree cover, indicating a substantial urban expansion. Conversely, agricultural land and wasteland have predominantly decreased, with the transformation of these areas largely contributing to the expansion of built-up spaces.